Cost of treating ventilator-associated pneumonia post cardiac surgery in the National Health Service: Results from a propensity-matched cohort study. (May 2018) - Luckraz, Heyman; Manga, Na'ngono; Senanayake, Eshan L; Abdelaziz, Mahmoud; Gopal, Shameer; Charman, Susan C; Giri, Ramesh; Oppong, Raymond; Andronis, Lazaros
Background: Ventilator-associated pneumonia is associated with significant morbidity, mortality and healthcare costs. Most of the cost data that are available relate to general intensive care patients in privately remunerated institutions. This study assessed the cost of managing ventilator-associated pneumonia in a cardiac intensive care unit in the National Health Service in the United Kingdom. Methods: Propensity-matched study of prospectively collected data from the cardiac surgical database between April 2011 and December 2014 in all patients undergoing cardiac surgery (n = 3416). Patients who were diagnosed as developing ventilator-associated pneumonia, as per the surveillance definition for ventilator-associated pneumonia (n = 338), were propensity score matched with those who did not (n = 338). Costs of treating post-op cardiac surgery patients in intensive care and cost difference if ventilator-associated pneumonia occurred based on Healthcare Resource Group categories were assessed. Secondary outcomes included differences in morbidity, mortality and cardiac intensive care unit and in-hospital length of stay. Results: There were no significant differences in the pre-operative characteristics or procedures between the groups. Ventilator-associated pneumonia developed in 10% of post-cardiac surgery patients. Post-operatively, the ventilator-associated pneumonia group required longer ventilation (p < 0.01), more respiratory support, longer cardiac intensive care unit (8 vs 3, p < 0.001) and in-hospital stay (16 vs 9) days. The overall cost for post-operative recovery after cardiac surgery for ventilator-associated pneumonia patients was £15, 124 compared to £6295 for non-ventilator-associated pneumonia (p < 0.01). The additional cost of treating patients with ventilator-associated pneumonia was £8829. Conclusion: Ventilator-associated pneumonia was associated with significant morbidity to the patients, generating significant costs. This cost was nearer to the lower end for the cost for general intensive care unit patients in privately reimbursed systems.